Comprehensive Laboratory Evaluation of Crack Resistance for an Asphalt Rubber Stress-Absorbing Membrane Interlayer (AR-SAMI) - Ping Li; Wenju Peng; Shuaituan Tian; Zhaohui Liu; Junbin Liu; Shende Liu (Sustainability, 2023)
Reflective cracking is a common distress of semi-rigid base asphalt pavements and overlay pavement projects. An asphalt rubber stress-absorbing membrane interlayer (AR-SAMI) prepared by waste tires is an effective engineering solution for treating reflective cracking. This method can also reduce black pollution. However, there is no unified test method and index for crack resistance evaluation. In this work, AR-SAMIs with different air voids and gradations were investigated. A small beam bending test (BBT) at −10 °C and 15 °C, crack expansion SCB (CE-SCB) test, low-temperature SCB (LT-SCB) test, and Overlay Test (OT) were performed to evaluate the crack resistance of AR-SAMI comprehensively. Statistical analysis was also performed. Results showed that the crack resistance of AR-SAMI improved as the air voids decreased. The crack resistance of 10-A gradation with more fine aggregate was excellent. However, the AR-SAMI with more coarse aggregate had better crack extension resistance under the condition of pre-existing cracks. There are differences in the evaluation results of different test methods due to the various evaluation focus. The −10 °C BBT, CE-SCB, and OT were recommended to evaluate the crack resistance comprehensively. Research results can guide the evaluation method or index selection of crack resistance and the optimization of AR-SAMI mixture design under different working conditions.